Sensitivity analysis of ice motion near Adams Island - Sykes, J. F.; Miller-Cushon, J. D. (Canadian Geotechnical Journal, 1992)
The time-averaged motion of shore-fast ice near a small Arctic island is analysed through the solution of the momentum equation for the ice cover using the Galerkin finite element method coupled with an adjoint sensitivity formulation. A linear-viscous rheology is used. Shore boundaries were modeled by prescribing ice velocity components such that the ice velocity vectors at shore boundaries were directed towards the ice cover, normal to the shoreline. A sensitivity analysis using the adjoint methodology showed that the velocity of the ice near the island is strongly influenced by the magnitude of the prescribed boundary velocities. The surface shear stresses from wind and ocean currents and the ice viscosities over part of the modeled domain also have a significant influence. The influence of Coriolis acceleration and the mass of the ice are not significant. Key words : ice mechanics, momentum, viscous rheology, finite elements.